Contextual Teaching and Learning (CTL) in Islamic Religious Education: An Implementation Analysis - Fauzi Ananda; Fauziatun Azhima; Shopiana; Gunawan Syahputra; Nurmisdaramayani; Muhammad Ilham (Young Journal of Social Sciences and Humanities, 2026)
This study aims to analyze the implementation of the Contextual Teaching and Learning (CTL) approach in Islamic Religious Education (PAI) subjects to improve students' understanding and practice of religious values ​​in their daily lives. This study uses a literature study type of research by collecting related data on contextual components in Islamic Education learning in schools. The results of the study indicate that PAI learning with a contextual approach successfully transforms the learning process from mere memorization of material into a meaningful learning experience. Implementation is carried out through seven main components of CTL: constructivism, inquiry, questioning, learning communities, modeling, reflection, and authentic assessment. This approach has been proven to increase active student involvement, strengthen character, and make it easier for students to connect PAI materials (morals, fiqh, history) with the context of real-life everyday situations. Conclusion: Contextual Teaching and Learning (CTL) is an effective strategy to improve PAI learning outcomes both academically and affectively. This approach makes Islamic Education more relevant and applicable, thus producing students who are not only cognitively intelligent, but also have good morals in society.